(untitled) (Journal of the College of Languages (JCL), 2019)
It is noted in the title that the paper studies the viewpoint in the novel The Dog and the Long Night by the Iranian novelist Shahranoush Parsi Pour and in the novel Alibaba’s Sad Night by the Iraqi novelist Abdulkhaliq Ar-Rikabi. Both are well known novelists, and about whose stories and novels many critical books, MA theses, and Ph.D. dissertations have been written. Also, some of their literary works have won prizes. Here, the researcher shed light on the concept of viewpoint, its types, and its importance in novels in general. This was done along with tackling the two viewpoints in both novels, where similarities and differences were identified. For this end, the researcher has adopted the analytic-descriptive approach, which is being exploited along the comparative approach so as to identify similarities and differences in viewpoints in both novels. In conclusion, it was shown that both writers employed the internal viewpoint from the hero-teller’s view, and made use of contemporary styles of narration. آنگونه که از عنوان پژوهش بر میآید به بررسی تحلیلی زاویهی دید در رمان سگ و زمستان بلند نوشتهی نویسندهی ایرانی شهرنوش پارسی پور و رمان لیل علی بابا الحزین نوشتهی نویسندهی عراقی عبد الخالق الرکابی میپردازد. هر دو نویسنده، از نویسندگان برجستهی عراق و ایران محسوب میشوند، جاییکه دربارهی اغلب آثارشان، مقالههای نقدی و پایاننامهها نوشته شدند و بعضی از آثارشان چند جایزهی ادبی نیز بردند. نگارنده در این پژوهش سعی میکند به مفهوم زاویهی دید و انواع آن، اهمیت زاویهی دید در رمان، زاویهی دید در دو رمان مورد نظر و مشابهتها و تفاوتهاى میان آنها بپردازد. روش تحقیق، توصیفی ـــ تحلیلی است، همچنین از آمیزش دو شیوه، توصیفی ـــ تحلیلی و مقایسه ای، نقاط مشترک و اختلاف بین دو رمان از لحاظ زاویهی دید بحث و بررسی کند. نتایج این تحقیق نشان میدهد که هر دو نویسنده، در این دو رمان، زاویه دید درونی به شیوهی راوی ـــ قهرمان را به کار برده و از شیوههای داستانی معاصر استفاده میکنند.